GREEN SUPPLY CHAIN. DEVELOPING LOGISTICS WITH CARE FOR THE ENVIRONMENT - Mach, Błażej; Furtak, Aleksandra (Acta Universitatis Nicolai Copernici. Zarządzanie, 2020)
Significant environmental changes over the last few decades have influenced the perception of the supply chain. The increasing awareness of the public has definitely changed the perception of environmental performance, which has motivated entrepreneurs to adapt to new concepts. New methods and tools have been developed to support lower material consumption and reuse.